National Cultures and Politeness Strategies in Intercultural Communication Among Japanese and American Characters in “The Last Samurai” Movie: A Cross-Cultural Pragmatic Analysis - Eka Nurilaila; Sigit Ricahyono; Dwi Setyadi; Samsul Arifin (Universitas PGRI Madiun, 2020)
The study which is descriptive qualitative in nature, aims to investigate preference of politeness strategies by American and Japanese characters in “The Last Samurai movie and explain it in terms the national culture. Results show that the order of preference by Americans is: 1) BoP (11/50%), 2) PoP (7/31.8%), 3) NeP (3/13.6%), and 4) OfR (1/4.5%). That by the Japanese is: 1) OfR (18/60%), 2) BoR (6/20%), 3). NeP (6/20%), 4) PoP (0). American national culture and that of Japan which are different affect their preference of politeness strategies shown in “The Last Samurai” movie. In conclusion, language and culture affect each other. People coming from different language and culture communicate differently.